The Impact of Community Participation on Tourism Village Management and Sustainability: A Case Study in Wonokitri Village, Pasuruan - Alfi Muflikhah Lestari; Moh Khusaini; Qomariyatus Sholihah; Gatot Ciptadi (Environment and Natural Resources Journal, 2025)
This research explores the impact of community participation in tourism village management –represented through motivation, opportunity and ability - and its implications for sustainability. Tourism villages, as a local community participation movement, play an important role in promoting economic, social, environmental, and cultural welfare. This study uses a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis techniques and was conducted in Wonokitri Village, Tosari District, Pasuruan Regency, East Java, Indonesia. Data were collected through questionnaires from 100 local community respondents. The results showed that motivation, opportunity, and ability had a significant impact on tourism village management, with an r-square contribution of 61.4%. However, only tourism village management had a significant influence on sustainability, with an r-square contribution of 85.2%. These findings emphasize the importance of tourism village management through strategic planning, technology, innovation, and community involvement in creating tourism village sustainability. In addition, the main driving factors in effective management include motivation indicators such as awareness of preserving culture and the environment, as well as job and economic opportunities, and increased income. This research provides theoretical contributions by expanding the sustainability model based on tourism village management and providing operational guidelines for the government, managers, and local communities to encourage tourism villages as centers of sustainable economic growth, as well as cultural and environmental preservation.